Hard tissue thin‐sectioning techniques in vertebrate paleohistology: Review, synthesis and improvements - Andrea Cuccu; Teresa Calderón; Beatriz Azanza; Daniel DeMiguel (Methods in Ecology and Evolution)
Abstract Paleohistology provides a significant amount of information on the physiology and evolution of ancient organisms through the study of their fossilized tissues' microstructure. Such discipline has been increasingly applied in vertebrate research over the years, however comprehensive and up‐to‐date methodological resources are lacking. In the specific, technical expedients associated with mammal research are little mentioned and some standards and protocols are still needed for the homogenization of paleohistological research. This work includes a review and summary of current paleohistological techniques, and new proposals for the improvement of the most widely used protocols for the preparation and sectioning of hard tissues. We further expand the focus beyond the traditional techniques including expedients for dentognathic remains, fossil and extant. The guide provided herein covers the techniques necessary to produce a paleohistological thin section, providing step‐by‐step instructions along with insights for technicians and both beginners and experienced scientists. Although paleohistology is widely applied, its technical aspect is often overlooked. With this work, we considerably improve the learning process, help standardize paleohistological techniques and make them accessible to researchers, increasing scientists' awareness of thin‐sectioning techniques and encouraging the exploration of new methodologies in this field.